The Use of Video Call Sex in Fulfilling Sexual Desires: Jacques Lacan's Perspective - Freny Matahari, Frisky; Jamilah Mihardjha, Eli (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The emergence of digital technology, particularly online communication, has opened up new avenues for fulfilling sexual desires. Video call sex is one such phenomenon, offering an alternative for long-distance sexual interaction. Jacques Lacan's psychoanalytic concepts of the real, imaginary, and symbolic provide a unique lens for analyzing this phenomenon. This research aims to analyze the phenomenon of using video call sex to fulfill sexual desires according to Lacan's psychoanalytic perspective. This qualitative study employed in-depth interviews with three female participants who actively engaged in video call sex. The findings reveal that modern communication media have transformed traditional concepts of sexuality, enabling virtual activities like video call sex to fulfill sexual needs. Desire, as Lacan posits, is the primary motivator for engaging in video call sex. Sexual satisfaction in this context is not solely reliant on the physical presence of a partner but also on their mental image, or imagination. This unfulfilled desire continually demands satisfaction, leading individuals to repeatedly engage in such activities. Lacan's perspective suggests that video call sex has shifted from a need to a desire. This desire, residing in the realm of symbols and the unconscious, necessitates continuous fulfillment. This research contributes to the understanding of how technology shapes modern sexuality and how psychoanalytic concepts can offer insights into the motivations and dynamics of virtual sexual practices.